Queue System simulations and comparison with Formulas Using Parameters in Theater Queue 21 DM. - Dwi Yulianingsih (Jurnal Sistem Informasi, 2005)
We have a lot of queuing theory is applied in the field of business, industry, transportation and daily problems - another day. A queue occurs when the arrival rate is greater than the level of service. Feature - queuing system operating characteristics can be determined by simulation techniques using computer media or by using a simple formula queue parameters.Both methods are applied to the case of queue system in Theater 21 DM and the results will be compared. Data - observation data obtained from the system queue at the ticket window will be used as input data in both the above methods and the solution will eventually be compared to determine the level of service efficiency. In this study obtained results that the resolution of features - features of the operating system of queues with more efficient simulation techniques.